PENGEMBANGAN MODEL REKRUTMEN DAN SELEKSI CPNS UNTUK MENINGKATKAN KUALITAS SUMBER DAYA MANUSIA (SDM) DI KABUPATEN MALINAU KALIMANTAN UTARA - Marpaung, Olma Riris (Universitas Madura, 2016)
This study aims to describe the factors that influence the recruitment and selection in Malinau, and to formulate model development of the recruitment and selection of CPNS to improve the quality of Human Resources (HR) in Malinau District of North Kalimantan.This study uses the theory of recruitment and selection process, in which this research uses descriptive qualitative method. Location of the research conducted at the Regional Employment Agency (BKD). Data was collected through a preliminary observation, followed by field research that included interviews and documentation. Data analysis techniques used in this research is data analysis techniques of qualitative. From the findings, in this study concluded that the model of recruitment and selection process based centralized used by BKD in Malinau District in 2013 has not been implemented to the maximum. The problems of recruitment process include planning recruitment is not in accordance with local needs and methods of recruitment are less use the internet to announce the formation. The problems of selection process include the findings of education that are inconsistent with the educational qualifications, not conducted the Ability Test Field (TKB), a standard passing grade was not adapted to local capabilities, and the placement of the mismatch that caused some participants withdrew. Thus, the development of the model as a solution to these problems is recruitment and selection of CPNS based on regional characteristics, in which procurement of PNS is prepared and tailored to local needs, differentiation graduation boundary values for each region along with develop methods of recruitment to the online system and the CAT system to TKD.